Ceria decorated porous diatom-xerogel as an effective adsorbent for the efficient removal of Eriochrome Black T. (January 2020) - Sriram, Ganesan; Uthappa, U.T.; Rego, Richelle M.; Kigga, Madhuprasad; Kumeria, Tushar; Jung, Ho-Young; Kurkuri, Mahaveer D.
Abstract: Diatomaceous earth or diatom (DE) are naturally available and low cost micro particles with distinct porous structure were used as an adsorbent for the removal of a hazardous dye, Eriochrome Black T (EBT). The surface modification of these DE were performed by sol-gel and hydrothermal methods to obtain a series of adsorbents such as diatom-ceria (DC), diatom-silica xerogel (DX), and diatom-silica xerogel-ceria (DXC). A cauliflower like morphology structure of ceria was observed on DE and DX. The adsorption performance of EBT was conducted by varying various parameters such as pH, adsorbent dosage, initial concentration, contact time and ionic strength. The materials DE, DC, DX and DXC showed the EBT removal efficiencies of 52, 77, 20, and 93%, respectively. The maximum adsorption capacity (qm) of DE, DC, DX and DXC was found to be 13.83, 23.64, 0.2 and 47.02 mgg -1 for the adsorption of EBT, respectively. The selectivity of EBT towards DXC was evaluated by treating a mixture of anionic dyes. The dye removal experiments was performed in presence of inorganic salts, however the presence of these salts did not affect the removal efficiency of DXC. Furthermore, the reusability of DXC was studied by recycling it up to 5 times and even at 5th cycle a removal efficiency of ∼66.8% was found. Thus, these studies demonstrate that the DXC material could be a promising candidate for the removal of EBT via adsorption for real time application in water treatment. Graphical abstract: Image 1 Highlights: Diatom and diatom-xerogel surfaces were modified with ceria by hydrothermal method. The ceria modified diatom-xerogel (DXC) showed higher dye removal efficiency (93%). The maximum adsorption capacity of DXC was 47.01 mgg −1 for EBT dye. The dye removal efficiency of DXC has not been affected by co-existing salts. DXC showed high selectivity and reusability for EBT removal.